Penerapan Strategi Marketing Dalam Pembuatan Konten Menggunakan Softselling Dan Hardselling Pada Tiktok Untuk Meningkatkan Brand Awareness Kisana - R. Yuniardi Rusdianto; Andri Rizal Setiawan (Jurnal Riset dan Inovasi Manajemen, 2024)
Marketing strategy is an effective strategy to increase company brand awareness. As social media develops quite rapidly, many companies use social media to market and introduce their products. To be able to attract an audience on social media, one of which is Tiktok, you need content that is interesting and follows developments in trends. PT Otak Kanan is a company that operates in the creative industry sector and has subsidiaries, one of which is Kisana, which is a hair removal cream product brand. This brand has problems with branding that is not optimal because this brand is still relatively new. Therefore, this research aims to observe, find out, provide solutions, and be involved directly using the method of implementing active participant observation in creating content marketing using soft selling and hard selling on Tiktok to increase brand awareness. Social media also plays a key role in marketing for brand awareness. The results show that creating interesting creative content by implementing softselling and hardselling on social media platforms such as Tiktok can increase company brand awareness.